Prenatal diagnosis and molecular cytogenetic characterization of a chromosome 1q42.3-q44 deletion in a fetus associated with ventriculomegaly on prenatal ultrasound - Chih-Ping Chen; Tsang-Ming Ko; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Wen-Lin Chen; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a chromosome 1q42.3-q44 deletion in a fetus associated with ventriculomegaly on prenatal ultrasound, and we discuss the genotype-phenotype correlation. Case report: A 36-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XX,del(1) (q42.3q44). Simultaneous array comparative genomic hybridization analysis on uncultured amniocytes revealed arr 1q42.3q44 (234,747,397-246,081,267) × 1 [GRCh37 (hg19)] with an 11.33-Mb 1q42.3-q44 deletion encompassing RGS7, FH, CEP170, AKT3, ZBTB18 and HNRNPU. The parental karyotypes were normal. Prenatal ultrasound at 20 weeks of gestation revealed bilateral ventriculomegaly and dilation of the third ventricle. The pregnancy was subsequently terminated, and a malformed female fetus was delivered with characteristic facial dysmorphism. Postnatal conventional and molecular cytogenetic analyses confirmed the prenatal diagnosis. Polymorphic DNA marker analysis showed a paternal origin of the distal 1q deletion in the fetus. Conclusion: Fetuses with a chromosome 1q42.3-q44 deletion may present ventriculomegaly on prenatal ultrasound. Prenatal diagnosis of ventriculomegaly should include a differential diagnosis of chromosome 1q distal deletions, and aCGH is useful under such a circumstance.